2012
DOI: 10.1002/humu.22242
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Regulatory Defect in the Branched-Chain α-Keto Acid Dehydrogenase Complex Due to a Mutation in thePPM1KGene Causes a Mild Variant Phenotype of Maple Syrup Urine Disease

Abstract: This article describes a hitherto unreported involvement of the phosphatase PP2Cm, a recently described member of the branched‐chain α‐keto acid dehydrogenase (BCKDH) complex, in maple syrup urine disease (MSUD). The disease‐causing mutation was identified in a patient with a mild variant phenotype, involving a gene not previously associated with MSUD. SNP array‐based genotyping showed a copy‐neutral homozygous pattern for chromosome 4 compatible with uniparental isodisomy. Mutation analysis of the candidate g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
69
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 29 publications
6
69
1
1
Order By: Relevance
“…This reaction is the irreversible and rate-limiting step in BCAA metabolism, catalysed by the mitochondrial BCKD complex [55]. The pattern of association observed in this study mirrors that observed in maple syrup urine disease (MSUD), an inborn error of metabolism caused by rare loss-of-function mutations in genes encoding components of the BCKD complex [55] or its regulatory phosphatase [56]. In our GWAS of BCAA levels, the strongest association signal was located 21 kb upstream of the PPM1K gene, which encodes the mitochondrial phosphatase that activates BCKD [4951].…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…This reaction is the irreversible and rate-limiting step in BCAA metabolism, catalysed by the mitochondrial BCKD complex [55]. The pattern of association observed in this study mirrors that observed in maple syrup urine disease (MSUD), an inborn error of metabolism caused by rare loss-of-function mutations in genes encoding components of the BCKD complex [55] or its regulatory phosphatase [56]. In our GWAS of BCAA levels, the strongest association signal was located 21 kb upstream of the PPM1K gene, which encodes the mitochondrial phosphatase that activates BCKD [4951].…”
Section: Discussionsupporting
confidence: 60%
“…In our GWAS of BCAA levels, the strongest association signal was located 21 kb upstream of the PPM1K gene, which encodes the mitochondrial phosphatase that activates BCKD [4951]. Loss-of-function mutations of PPM1K in humans [56] or the knock-out of its ortholog Ppm1k in mice models [35] results in impaired BCKD activity and high levels of BCAAs and branched-chain alpha-ketoacids, a pattern that resembles that observed for common PPM1K genetic variants in our study. Therefore, it is plausible that the genetic variants identified in this study act by impairing the catabolism of BCAAs, hence leading to higher circulating levels of these amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin is the chief regulator of amino acid metabolism and changes in fasting BCAA levels may be regulated by the effect of insulin on the rate of appearance and clearance of BCAA together with a decreased activity of catabolic enzymes [2]. Loss-of-function mutations in PPM1K in humans [21], and disruption of key BCAA metabolism in obese mice and Zucker rats, exhibit a reduced expression of the mitochondrial isoform of branched chain-amino-acid transaminase (BCAT2; which catalyses the first and reversible step in BCAA catabolism), and mitochondrial branched chain α-keto acid dehydrogenase (BCKD) complex E1-α (which catalyses the rate-controlling and the first irreversible step), leading to increased plasma BCAA levels [22,23]. A decreased BCAA metabolism in fat tissue may contribute to higher BCAA levels in individuals with insulin-resistant obesity [2,[22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Protein phosphatase 2C in mitochondria (PP2Cm) is a mitochondrial matrix-targeted serine/threonine protein phosphatase encoded by the gene PPM1K [1,2] . It is a member of the protein phosphatase 2C family and is highly conserved among vertebrates.…”
Section: Introductionmentioning
confidence: 99%